Perbedaan Kematangan Karier Mahasiswa Tahun Masuk 2014 Fakultas Ilmu Pendidikan Universitas Negeri Padang ditinjau dari Gaya Pembuatan Keputusan dan Jenis Kelamin - Violina, Erwita Ika; Daharnis, Daharnis; Marjohan, Marjohan (Universitas Negeri Padang, 2015)
Career maturity is readiness of individuals to deal with the tasks of the development of his/her career. Student’s development career task is make his/her education as a career direction. This study aims to describe career maturity of the Faculty Education Universitas Negeri Padang students class 2014, according to decision making style and gender. Population of this research is 336 students of Faculty Education Universitas Negeri Padang, with samples are 183 students choosen by proportional random sampling. The instruments used in this research is the career maturity scale and Assessment of Career Decision Making of Harren (1979). The results of this research are: 1) student’s career maturity are different significantly according to decision making style, 2) student’s career maturity aren’t different according to gender, 3) there isn’t interaction of decision making style and gender in explaining student’s career maturity.